2020
DOI: 10.1016/j.euroecorev.2020.103444
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, the jobs ladder and economic mobility

Abstract: Globalization affects the mix of jobs available in an economy and the rate at which workers gain skills. We develop a model in which firms differ in terms of productivity and workers differ in skills, and use the model to examine how globalization affects the wage distribution and the career path of workers as they move up the jobs ladder. We calibrate the model using many of the same parameters and targeting the same moments of the US economy as Melitz and Redding (2015) and then investigate the impact of glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…The survey revealed that the majority of the respondents (86.9) agree that globalization is a concept of duality, having both merits and demerits. (d) Benefits from globalization far outweigh its shortfalls and excesses, corroborating the assertion of Davidson, et al (2020) that globalization by all standards has contributed more to global development. While 60.8% of respondents suggest that the benefits of globalization far outweigh the demerits, 39.2% disagree.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The survey revealed that the majority of the respondents (86.9) agree that globalization is a concept of duality, having both merits and demerits. (d) Benefits from globalization far outweigh its shortfalls and excesses, corroborating the assertion of Davidson, et al (2020) that globalization by all standards has contributed more to global development. While 60.8% of respondents suggest that the benefits of globalization far outweigh the demerits, 39.2% disagree.…”
Section: Discussionsupporting
confidence: 63%
“…9% think otherwise as suggested by Kay (2004). The test reveals that 86.9 percent of respondents overwhelmingly agree that globalization is actually a two-edged sword that cuts from both sides to that end bringing both benefits and burdens to humanity in its implementation (Davidson, et al, 2020;Weidenbaum & Batterson, 2001). The author accepts the result that is in keeping with the worldview since the phenomenon has inured to global development amidst the shortfalls.…”
Section: Research Approach/sample Size/sampling Techniques and Resear...mentioning
confidence: 98%
See 3 more Smart Citations